An integrated conceptualization of content in an information society. (September 2016) - Hanafizadeh, Payam; Yarmohammadi, Maryam
Content is the origin of communications. It is also one of the key indices in the evaluation of societies' economic development. However, review of the literature reveals no agreed conceptualization of content. Lack of consensus regarding the definition of content, on the one hand, coupled with its significant role as a developmental determinant for an information society, on the other, were motives behind the proposed integrated definition of content presented in this study. Our suggested conceptualization of content is referred to as "Triple Cs", and is composed of 3 elements: (1) cerebral process, (2) conduit(s), and (3) conduitee.